The Paleozoic Evolution of the Olga Basin Region, Northern Barents Sea: A Link to the Timanian Orogeny. (1st February 2019) - Klitzke, P.; Franke, D.; Ehrhardt, A.; Lutz, R.; Reinhardt, L.; Heyde, I.; Faleide, J. I.
Abstract: The evolution of the Olga Basin region in the northern Norwegian Barents Sea and its relation to the Caledonian and Timanian orogenies is poorly understood due to sparse geophysical data and the lack of well control. In 2015, the German Federal Institute for Geosciences and Natural Resources (BGR) acquired deep multichannel seismic lines as well as gravity and magnetic data. The new seismic data reveal that the Olga and Sørkapp Basins evolved as a W‐E striking half‐graben system along a major normal fault in the north and a smaller normal fault in the south, respectively. Deep crustal undulating high‐amplitude reflections below the Olga and Sørkapp Basins coincide with W‐E striking local magnetic maxima and may imply that the basins evolved on top of old collisional fabrics. The absence of major compressional deformation implies a post‐Caledonian onset of subsidence. The W‐E structural configuration of the sedimentary basins is difficult to reconcile with an earlier proposed NE striking Caledonian branch in the northern Barents Sea. Instead, the orientation of the Olga and Sørkapp Basins lines up with Timanian structural trends from the Pechora Basin. We propose that the Olga and Sørkapp Basins experienced transtensional deformation during the late Devonian/early Carboniferous NE‐SW regional extension phase whereby inherited Timanian lineaments controlled the final W‐E basin configuration. A salient pre‐Caledonian Olga‐Sørkapp crustal block in the central Barents Sea would also explain the recently proposed NNW rotation of Caledonian nappes and thrust sheets in the southwestern Barents Sea. Key Points: Combined analysis of seismic reflection and potential field data reveal a W‐E oriented basin system in the NE Norwegian Barents Sea including the Olga and Sørkapp Basins Local potential field maxima delineate the Olga and Sørkapp Basins and indicate deep crustal heterogeneities Both basins evolved as half‐grabens and are underlain by Timanian basement that controlled the later subsidence evolution